The family's experience of the child and/or teenager in palliative care: fluctuating between hope and hopelessness in a world changed by losses - Maira Deguer Misko; Maiara Rodrigues dos Santos; Carolliny Rossi de Faria Ichikawa; Regina Aparecida Garcia de Lima; Regina Szylit Bousso (Universidade de São Paulo, 2015)
OBJECTIVES: to understand the family's experience of the child and/or teenager in palliative care and building a representative theoretical model of the process experienced by the family.METHODOLOGY: for this purpose the Symbolic Interactionism and the Theory Based on Data were used. Fifteen families with kids and/or teenagers in palliative care were interviewed, and data were collected through semi-structured interviews.RESULTS: after the comparative analysis of the data, a substantive theory was formed "fluctuating between hope and hopelessness in a world changed by losses", composed by: "having a life shattered ", "managing the new condition", "recognizing the palliative care" and "relearning how to live". Hope, perseverance and spiritual beliefs are determining factors for the family to continue fighting for the life of their child in a context of uncertainty, anguish and suffering, due to the medical condition of the child. Along the way, the family redefines values and integrates palliative care in their lives.CONCLUSION: staying with the child at home is what was set and kept hope of dreaming about the recovery and support of the child's life, but above all, what takes it away even though temporarily is the possibility of their child's death when staying within the context of the family.